Analisis Dampak Ketersediaan Sarana Publik terhadap Perekonomian Masyarakat Kabupaten Aceh Timur - Asyura, Asyura; Iskandar, Iskandar; Asnidar, Asnidar (Journal of Economics, Bussiness and Management Issues, 2025)
This study aims to analyse the impact of the availability of public facilities on the community's economy in East Aceh Regency. The method used in this research is descriptive analysis with asample of 96 respondents. research data sources consistof primary and secondary data. The primary data is information obtained directly through interview interactions based on questionnaires with respondents, photographs and visual observations. While secondary data is data obtained from BPS. Data processing and analysis were carried out using SPSS 25 software.The results of the analysis show that public facilities have an average (mean) value of 29.3958 with a standard deviation of 3.82644. Meanwhile, the community economy variable has an average value of 21.8750 with a standard deviation of 2.30902. This finding indicates that public facilities have asignificant influence on the economy of traders in the Idi Rayeuk office centre area.Thus, it can be concluded that the central office area in Idi Rayeuk, East Aceh Regency, is used by traders as a strategic location to run their businesses. The existence of public facilities contributes to the improvement of the community's economy, which is reflected in several indicators, such as increased income, increased employment opportunities, and the fulfilment of various community needs.